2007
DOI: 10.3201/eid1312.070275
|View full text |Cite
|
Sign up to set email alerts
|

Host-Feeding Patterns ofCulexMosquitoes in Relation to Trap Habitat

Abstract: Mosquito feeding patterns identify vertebrate species potentially involved in the amplification of West Nile virus. In New York, northern cardinals (Cardinalis cardinalis) were the predominant hosts in most habitats. Crow (Corvus sp.) blood meals were most frequently identified from sewage treatment plant and storm water catch basin habitats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
(22 reference statements)
3
19
0
Order By: Relevance
“…pipiens varies considerably by region (35-96%). 7,16,40,53,54 We documented an unusually high rate of human feeding by Cx. pipiens (16% of total blood meals).…”
Section: Discussionmentioning
confidence: 94%
“…pipiens varies considerably by region (35-96%). 7,16,40,53,54 We documented an unusually high rate of human feeding by Cx. pipiens (16% of total blood meals).…”
Section: Discussionmentioning
confidence: 94%
“…pipiens as the primary enzootic vector in this region. Culex pipiens has been established as an important enzootic vector by consistent isolations of WNV from mosquito trap collections [11,13,20], by its ornithophilic feeding behaviour [13,40,41], and associations between virus-infected mosquitoes and dead bird reports [42][43][44][45][46]. This species has also been incriminated as a bridge vector in Illinois [47].…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have previously shown similar heterogeneity in mosquito feeding patterns, [2][3][4][5][6][7]34 our study is the first to show such heterogeneity at the host species level for Cs. melanura , the primary enzootic vector of EEEV.…”
Section: Discussionmentioning
confidence: 79%
“…To date, however, such studies have been largely restricted to potential vectors of WNV. [3][4][5][6][7] The extent to which observations from studies of WNV can be applied to other mosquito-borne pathogen systems for which birds serve as reservoir hosts is uncertain, because these pathogens vary in the ecological factors that influence transmission. 11 The ecology of the transmission dynamics of eastern equine encephalitis virus (EEEV) is distinct from that of WNV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation